2022
DOI: 10.1155/2022/4254605
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter suis-Associated Gastritis Mimicking Conventional H. pylori-Associated Atrophic Gastritis

Abstract: A 45-year-old Japanese man underwent esophagogastroduodenoscopy, which revealed spotty redness at the gastric fornix, mucosal swelling, diffuse redness in the corpus, and mucosal atrophy in the gastric angle and antrum. Histological examination showed rod-shaped bacteria that appeared larger than Helicobacter pylori. The patient tested positive for rapid urease test, and serum anti-H. pylori IgG antibody test results were negative. Further examination of the bacteria revealed that H. suis antibody test was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The gastric MALT lymphomas are most probably the consequence of the continuous long-term stimulation of lymphocyte proliferation and are naturally not related to hypergastrinemia, since lymphocytes do not express the gastrin receptor or receptors for any of the ECL cell mediators (no lymphoma was detected in patients with gastrinoma). Interestingly, Helicobacter suis can infect humans and give rise to gastric MALT lymphoma ( 42 ), and may also induce gastritis, mimicking H. pylori gastritis ( 43 ).…”
Section: Gastric Cancermentioning
confidence: 99%
“…The gastric MALT lymphomas are most probably the consequence of the continuous long-term stimulation of lymphocyte proliferation and are naturally not related to hypergastrinemia, since lymphocytes do not express the gastrin receptor or receptors for any of the ECL cell mediators (no lymphoma was detected in patients with gastrinoma). Interestingly, Helicobacter suis can infect humans and give rise to gastric MALT lymphoma ( 42 ), and may also induce gastritis, mimicking H. pylori gastritis ( 43 ).…”
Section: Gastric Cancermentioning
confidence: 99%
“…They concluded that H. suis was the most common NHPH that infected human stomachs 13 . The H. suis infection leads to diseases such as gastric mucosa-associated lymphoid tissue (MALT) lymphoma, nodular gastritis, chronic gastritis, and peptic ulcer [14][15][16][17][18][19][20] . However, the above reports did not provide proof of H. suis or other NHPH infection because they only used PCR assay and did not isolate the bacteria or analyze the isolated bacteria's genome to identify the infecting bacteria.…”
Section: Introductionmentioning
confidence: 99%